A sensitive method for the determination of levamisole in serum by electrochemiluminescence. (7th May 2013) - Xiao, Ying; Li, Jianping; Fu, Cong
ABSTRACT A novel method was developed for the determination of levamisole by electrochemiluminescence. The method was based on electrochemiluminescence signal enhancement produced by Ru(bpy)32+, which reacted with the tertiary amine group of levamisole on a platinum electrode in 12 mmol/L borate buffer (pH 9). A linear relationship between the luminous intensity and concentration of levamisole in the range 0–1 × 10–7 mol/L was obtained and the detection limit was 1.76 × 10–11 mol/L. The method is sensitive, selective, simple and convenient. The method has been successfully applied to the analysis of levamisole in serum. Copyright © 2013 John Wiley & Sons, Ltd.